PENGARUH KUALITAS PRODUK, HARGA, DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN KUKUS SINGKONG KEJU MOJOKERTO - Hidayat, Fuad; Maduwinarti, Ayun; Handayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2016)
Many ways are done by someone in starting or running a business activity such as making your own product to be sold. These activities are more advantages compared to systems or other business activities. So we are interested to do business using their own how to create products that will be sold. One way to increase the purchasing decision is to improve the quality, competitive price and also offer unique packaging. The purpose of this study was to Knowing how much influence packaging, price and quality to the food purchasing decisions steamed cassava cheese mojokerto. Variables to be studied is the packaging, quality and price. Methods of data collection by observation, literature study and questionnaire. Data analysis techniques used in this research is multiple linear regression method. The population of this research is the students, Housewife, civil servants / private and entrepreneurial in Mojokerto. The number of respondents who assigned as many as 100 respondents. Based on calculations it can be concluded that variable quality of 2,970 >1,985 tabel, the price of 2,602 >1,985 tabel and packaging by,2,216 > table 1,985 Keywords: Pricing, Packaging, Product, Quality, Yams